(untitled) (Journal of the College of Basic Education, 2022)
Iraq has been of great strategic importance in the American strategic thought as a product and a natural reflection of what its land contains of natural resources, in addition to its geopolitical position as it mediates the most important vital regions of the world, and the center of the convergence of global strategies, so Iraq was one of the most prominent countries that received the attention of successive American administrations Since the second half of the nineteenth century, its interest has increased, after the Second World War ended on September 2, 1945. The regions of the Middle East were unknown to the Americans aspiring after independence in 1783 to extend their activity to the continents of the ancient world, except for little information about Mesopotamia, Egypt, which they read about its history and civilization and its being a road linking Asia, Africa and Europe, and the American activity began with the modern renaissance led by Muhammad Ali Pasha in Egypt In the first half of the nineteenth century.